Entrepreneurship education in Africa : a contextual model for competencies and pedagogies in developing countries - Mbeteh, Alfred; Pellegrini, Massimiliano M. (Emerald Publishing Limited, 2022)
Entrepreneurship education as a potential antecedent of entrepreneurial spirit has too often been limited to Western theories. Entrepreneurship Education in Africa contributes to the body of knowledge of entrepreneurship education and youth entrepreneurship. The book uses Sierra Leone as a case study which dynamics are similar to other developing countries in Africa and around the world. Presenting a contextual approach to entrepreneurship education in resource-bounded contexts such as those currently faced by African countries, and in general, by developing countries, Mbeteh and Pellegrini offer a unique framework based on entrepreneurial competences and pedagogical approaches as a structure to build effective entrepreneurship education programmes within developing countries. Serving as a reference point for future researchers to engage with entrepreneurship education in developing countries, and occupying a gap in current research, Entrepreneurship Education in Africa is an important resource for scholars and professionals interested in business, entrepreneurship, and education. The Entrepreneurial Behaviour series is focused on expanding the scope of Entrepreneurial Behaviour theory and analysis and enriching practice by encouraging multi-cultural and multi-disciplinary approaches.
Keywords: Entrepreneurship -- Study and teaching -- Africa.; Entrepreneurship -- Study and teaching -- Sierra Leone.; Business education -- Africa.; Business education -- Sierra Leone.; Business & Economics -- Entrepreneurship.; Entrepreneurship.; elektronické knihy; electronic books